Analisis Awal Temuan Rangka BatCkt1 dari Situs Cikuntul - Andi Muh. Farhan Alfiansah (Badan Riset dan Inovasi Nasional (BRIN), 2024)
Abstract The excavations were carried out by the Research Team of the National Archaeological Research Center (now BRIN) in 2009 and 2010 at the Cikuntul Site, Karawang Regency, West Java. These activities have found some human remains which was involved in this area in Protohistoric times. The finding of human remains from an archaeological site should be documented for the next research. Exploration that has been carried out at the Cikuntul Site has resulted in the presumption that the site is a remnant of the late Prehistoric civilization on the North Coast of West Java. The descriptive-qualitative method are used in this study that is carried out by observing the anatomical remains of Individual BatCkt1 as an individual with the most complete skeletal preservation from the Cikuntul Site. The description focus on the anatomical condition of the Individual BatCkt1 and determination of population affinity.